Effectiveness of QR-Based Modified Strategic Intervention Materials in Improving the Academic Performance of SHS Students in Disciplines and Ideas in the Social Sciences - Pecson, Ryan (CV. Samuel Manurung and Co, 2025)
21st-century learners nowadays are at their best when their instructional materials are diverse, contextualized, and technology-based. With such intention in mind, the study determines the effectiveness of the developed QR-based modified strategic intervention materials in improving the academic performance of senior high school students in the subject Disciplines and Ideas in the Social Sciences in the Humanities and Social Sciences strand in the Philippines. Using the experimental research method, specifically the one-group pretest-posttest design, 75 SHS students are pre-assessed for their academic performance in the subject focused on their least mastered competencies. After the pretest, the top three least-mastered competencies were identified, which included the topics of the MSIMs to be developed, as well as the 27 students needing intervention. After three expert validators rated the developed QR-MSIMs, pilot testing commenced. After the implementation, a posttest is conducted to compare the academic performance of the students before and after their exposure to the intervention materials. Before the use of QR-MSIMS, SHS students performed poorly in DISS, indicating the need for remediation or intervention. Significantly, the SHS students improved their academic performance after using the QR-MSIMs, leading to the acceptance of the alternative hypothesis and further cementing the effectiveness of the treatment or intervention materials in enhancing the least-mastered competencies of the students. The study recommends further use of the QR-MSIMs in other social sciences disciplines, as well as in various learning contexts through action research, where the results can be disseminated further during in-service training or learning action cell sessions